2004
DOI: 10.1007/s10327-003-0091-6
|View full text |Cite
|
Sign up to set email alerts
|

Selection of an attenuated isolate of Bean yellow mosaic virus for protection of dwarf gentian plants from viral infection in the field

Abstract: An attenuated isolate of Bean yellow mosaic virus (BYMV), designated B-33, that caused barely any mottling on the leaves of gentian plants (Gentiana scabra) was isolated from dwarf gentian plants. Infection with this isolate did not cause severe symptoms in several leguminous plants or in prairie gentian (Eustoma grandiflorum) plants. Dwarf gentian plants that had been infected with an inoculum of partially purified B-33 were propagated vegetatively from cuttings without difficulty. The B-33 isolate could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…An aphidborne virus, Bean yellow mosaic virus (BYMV) causes a mosaic, atrophic disease, which is a serious problem for gentian producers in this prefecture (Uga et al 1998(Uga et al , 2002. An attenuated isolate of BYMV, B-33, was developed to cross-protect plants from more damaging strains of BYMV (Uga et al 2004). Because B-33 is serologically indistinguishable from other isolates of BYMV, we previously developed a reverse transcription-polymerase chain reaction (RT-PCR)-restriction fragment length polymorphism (RFLP) technique to distinguish B-33 from the virulent isolates 35-1 and No.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An aphidborne virus, Bean yellow mosaic virus (BYMV) causes a mosaic, atrophic disease, which is a serious problem for gentian producers in this prefecture (Uga et al 1998(Uga et al , 2002. An attenuated isolate of BYMV, B-33, was developed to cross-protect plants from more damaging strains of BYMV (Uga et al 2004). Because B-33 is serologically indistinguishable from other isolates of BYMV, we previously developed a reverse transcription-polymerase chain reaction (RT-PCR)-restriction fragment length polymorphism (RFLP) technique to distinguish B-33 from the virulent isolates 35-1 and No.…”
mentioning
confidence: 99%
“…4 were obtained from dwarf gentian plants in Saitama Prefecture, Japan (Uga et al 2004). A BYMV-infected gentian leaf (0.1 g) was ground with a flatbottomed 3 ϫ 12 cm test tube in a polyethylene bag (BAG PE 01mm 75 ϫ 130, AS ONE, Osaka, Japan) with 1 ml of extraction buffer (50 mM Tris-HCl, pH 7.5) at room temperature.…”
mentioning
confidence: 99%
“…RT-PCR-RFLP was reported to be a reliable method for evaluating the effi cacy of attenuated strains of several plant viruses (Fuji et al 2000;Nakazono-Nagaoka et al 2005;Uga et al 2004). A comparison of the nucleotide sequences of KM3 and 16 other CYNMV isolates (Kondo et al 2003) revealed that two base substitutions at positions 195 and 1028 are specifi c to KM3 (Fig.…”
Section: Discrimination Of Attenuated Strain Km3 From Other Cynmv Isomentioning
confidence: 96%
“…There has been some research on the use of attenuated strains [e.g., Citrus tristeza virus (Costa and Müller 1980), Japanese yam mosaic virus (Fuji et al 2000;Kajihara et al 2000), and Bean yellow mosaic virus (Uga et al 2004)] to protect perennial plants. Each of these attenuated strains was selected from native isolates occurring naturally in the fi eld.…”
Section: Discrimination Of Attenuated Strain Km3 From Other Cynmv Isomentioning
confidence: 99%
See 1 more Smart Citation